Leaf Phenotypic Variation of Chuanqian Crape Myrtle in Natural Populations - Siwen Hao; Donglin Zhang; Yafeng Wen (HortScience)
Leaves are the primary tissue for photosynthesis and transpiration, playing an irreplaceable role in the ecosystem. Understanding variations in leaf morphology across different populations is crucial for better insight into plant classification, evolution, and cultivation practices. From 10 populations of Lagerstroemia excelsa and 80 individual specimens, we measured key leaf traits, including leaf length (LL), leaf width (LW), leaf area (LA), leaf circumference (LC), leaf basal angle (LBA), and leaf vein angle (LVA), to determine the geographic variation trends in leaf morphology across natural populations. Our results revealed several important findings: 1) significant differences in leaf morphology were observed among the populations; 2) temperature appears to be a primary factor influencing the potential geographic distribution of L. excelsa; 3) the 10 populations were grouped into two main categories, indicating that similar germplasm tends to be distributed contiguously. These insights are valuable for future efforts in the introduction, breeding, selection, and cultivation of L. excelsa.